CAR T-Cell Therapies in Italy: Patient Access Barriers and Recommendations for Health System Solutions - Jommi, Claudio; Bramanti, Stefania; Pani, Marcello; Ghirardini, Alessandro; Santoro, Armando (Frontiers in Pharmacology, 2022)
CAR T-cell therapy has emerged as a potentially transformative immunotherapy for certain B-cell malignancies including relapsed / refractory diffuse large B-cell lymphoma (DLBCL). Unhindered and appropriate access for eligible patients is essential to enable optimal outcomes and depends on effective interplay of stakeholders and processes along the patient’s therapeutic journey. In Italy, CAR T-cell therapies have been awarded innovation status by the Italian Medicines Agency (AIFA) and were integrated into routine patient care under specific criteria. However, our analysis indicates that fewer than one in five DLBCL patients eligible under the EMA authorization, or around one in three DLBCL patients eligible under the AIFA criteria, received treatment with a licensed CAR T-cell therapy product in 2020. This publication describes key patient access barriers to CAR T-cell therapies in Italy and provides recommendations on potential solutions at the health system level.